A qualitative inquiry of speech-language therapists’ views about breastfeeding management - Danica Schlome; Esedra Krüger; Bhavani Pillay (South African Journal of Communication Disorders)
Background: Management of oropharyngeal dysphagia within the first few days of an infant’s life results in favourable breastfeeding outcomes, indicating the importance of investigating the breastfeeding management practices of speech-language therapists (SLTs) working within this field.